Design on modified-zinc anode with dendrite- and side reactions-free by hydrophobic organic-inorganic hybrids for ultra-stable zinc ion batteries. (1st December 2022) - Liu, Mao-Cheng; Tian, Chen-Yang; Zhang, Dong-Ting; Zhang, Yu-Shan; Zhang, Bin-Mei; Wang, Yuan-Yi; Li, Chen-Yang; Liu, Ming-Jin; Gu, Bingni; Zhao, Kun; Kong, Ling-Bin; Chueh, Yu-Lun
Abstract: Zinc has been widely deployed as an anode of zinc ion batteries (ZIBs) due to high safety, high theoretical capacity, and low potential. However, dendrite growth and side reactions still severely hampered scale-up implementation in ZIBs. Here, organic hydrophobic polyvinylidene fluoride and inorganic Santa Barbara Amorphous-15 (PVDF-SBA15) hybrids were designed as a surface modification layer to stabilize Zn anode, leading to an optimized Zn/electrolyte interface with large-scale feasibility. The PVDF-SBA15 surface modification realizes synergistic protection on zinc anode since the hydrophobic PVDF could avoid the side reactions through prevention of direct contact between the zinc and the electrolyte, while the evenly distributed porous structure of SBA15 can induce uniform zinc plating/stripping and inhibit dendrite growth by uniform zinc ions flux. The hydrophobic PVDF-SBA15 surface-modified Zn anode (PVDF-SBA15 @Zn) exhibits dendrite-free Zn plating/stripping with low overpotential after 1650 h at a current density of 3 mA cm −2 in symmetrical batteries. The PVDF-SBA15 @Zn||V2 O5 full batteries enable the stable cycling of 82.14 % capacity retention after 1000 cycles compared with 23.55 % of Zn||V2 O5 . The effectively inhibited dendrite growth and side reactions on Zn anode through hydrophobic organic-inorganic surface modification layer provide solid foundation for the realization of ultra-stable zinc ion batteries. Graphical Abstract: ga1 Highlights: Hydrophobic PVDF-SBA15 coating was constructed to synergistically avoid dendrite growth and side reactions on the Zn anode. The PVDF-SBA15@ZnZn anode exhibits dendrite-free Zn plating/stripping with a low overpotential of 39 mV after 3800 h. The PVDF-SBA15@Zn||V2 O5 batteries enable the stable cycling of 82.14 % capacity retention after 1000 cycles compared with 23.55 % of Zn||V2 O5 .